2017
DOI: 10.1080/14616734.2017.1383489
|View full text |Cite
|
Sign up to set email alerts
|

A short-term longitudinal study of correlates and sequelae of attachment security in autism

Abstract: In this short-term longitudinal study, 30 preschool-aged children with autism were first observed in Ainsworth’s Strange Situation Procedure and, separately, interacting with the primary caregiver in the home. One year later, each child completed both a developmental assessment and an observational assessment of empathic responding. Behaviors typical for children with autism were distinguished from behaviors suggestive of relationally based attachment disorganization. Forty-five percent of the children were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 69 publications
1
18
0
3
Order By: Relevance
“…The increased eye contact with parents is in line with prior work showing that children with ASD are just as likely as typically developing children to have a secure attachment style with their parents (Rogers, Ozonoff, & Maslin-Cole, 1991;Rozga et al, 2018;Sigman & Mundy, 1989). Our results are also consistent with literature demonstrating that children display clear preferences early in life for their parents over unfamiliar adults (Dixon et al, 1981;Melinder, Forbes, Tronick, Fikke, & Gredeback, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The increased eye contact with parents is in line with prior work showing that children with ASD are just as likely as typically developing children to have a secure attachment style with their parents (Rogers, Ozonoff, & Maslin-Cole, 1991;Rozga et al, 2018;Sigman & Mundy, 1989). Our results are also consistent with literature demonstrating that children display clear preferences early in life for their parents over unfamiliar adults (Dixon et al, 1981;Melinder, Forbes, Tronick, Fikke, & Gredeback, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…For instance, stereotypic behaviors would be discounted by trained coders if they suspect that the infant has a neurological or developmental disorder (e.g. Capps, Sigman, & Mundy, 1994; Rozga et al, in press; Dozier & Bernard, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The study found that with severe manifestations on the mother's side of anxiety, insensitivity to the child's signals, rigidity, intrusiveness and unpredictability in the interaction, the presence of negative physical contact with the child, as well as irritation, a low level of reciprocity and organization of the interaction process; a large number of different behavioral disorders are noted in a child. Interpreting these results from a systemic point of view, we can conclude that, when faced with the negative manifestations of the parent, the child's anxiety and / or fear intensifies (Belsky, 2005;Cibralic et al, 2018;McKenzie & Dallos, 2017;Rozga et al, 2018). These feelings reduce the quality of their attention, can enhance the desire to avoid, distance themselves from interaction, and also manifest themselves in defiant behavior, the function of which can be to respond to feelings of fear, anxiety or anger.…”
Section: Resultsmentioning
confidence: 93%